Catholics, British Labour and Spain : Mgr. Hinsley answers difficulties (press cutting)
019-0016-001 From "CATHOLIC HERALD", November 6, 1936. CATHOLICS, BRITISH LABOUR AND SPAIN Mgr. Hinsley Answers Difficulties Documentary Evidence Of Communist Plot Catholics To Remain In Their Trade Unions (EXCLUSIVE) On Monday the Daily Herald printed the news of an interview accorded by the Archbishop of Westminster to a deputation of Catholic Trade Union officials under the heading "Dr. Hinsley Reassures Labour." The report, in which it was stated that Mgr. Hinsley "urged that Catholic workers should be members of their appropriate trade-unions," was substantially true. It was, however, only half the story and used by the Labour paper to reassure Catholic Labour sympathisers on eve of the Municipal Elections. The Catholic Herald is able to give the full story, which arises from the problems created in the consciences of Catholic Labour sympathisers by the Spanish conflict. Mgr. Hinsley was, in fact, not dealing with any election issues, but answering with great kindness and sympathy difficulties put to him by a number of prominent Catholic leaders in the Labour and Trade Union movements. The attitude of Catholic Labour is also expressed on p. 9 in a letter from a member of the executive of the Reading Labour Party, the various points in which are fully discussed and answered. DIFFICULTIES SUMMARISED AND ANSWERED Arising out of a talk at the recent dinner in honour of Mr. Ben Tillett in which the Archbishop of Westminster promised to have an informal interview with some Catholic leaders, unofficially representing Catholics with Labour sympathies, Mr. T. O'Brien, the General Secretary of the Association of Theatrical Employees sent a letter to Archbishop's House in which difficulties at present being felt by Catholics in the Labour movement were outlined. Members of Delegation The points in this letter formed the basis of the interview of last Saturday evening when Dr. Morgan, Medical Adviser of the T.U.C.; Miss Annie Somers, Regional London Organiser of the Labour Party; Mr. Bernard Sullivan, London Organiser of the Tailors and Garment Workers' Union; Mr. H. Young, of the Union of Post Office Workers; Mr. F.J. Lavery, of the Transport Catholic Guild and Mr. T. O'Brien, met his Grace. Disloyalty to Labour Points raised in the letter were as follows: 1. The atrocities alleged to have occurred in the early stages of the Spanish Civil War had, it was felt, been used by certain British papers as a means of alienating the sympathy and loyalty of Catholics in the British Labour Movement against that Movement. There was Mgr. Hinsley's lead to Catholic Action in England by the co-ordination of societies and the appointment of Dr. O'Donovan as Lay-President, are described on page 3. a grave doubt as to whether the outcry against the Spanish atrocities was genuinely pro-Catholic, or whether the situation was being used for purely political motives, by connecting Labour with Communism. 2. It was believed by many Catholics that the situation in Spain had been brought about, not by Communist influence but by a military rising against a legitimate government. Church in Spain 3. Many Catholics and the workers at large believed that the Church in Spain was a participant in the uprising, while the Spanish Hierarchy opposed the constituted Goverment on economic rather than spiritual grounds. 4. It was also believed by those who had no means of rebutting the impression that the Church in Spain had not attempted to remedy the oppression of the Spanish workers and had failed vigorously to advocate the Social teaching of the Popes. The Church and Fascism 5. The impression was gaining momentum that the Church was lining up with what was known as Fascism, in order to stave off the menace of Communism. Meanwhile the feeling of many was that Fascism destroyed God and religion by a process of vivisection, while Communism destroyed it by a process of annihilation - a choice that gave little consolation. 6. The British Labour Movement considered the present Government in Spain to be democratic and duly constituted, while the Rebellion was Fascist, using religious bias. Catholic workers in Britain were members of their various Trade Unions and local Labour Parties, having to work in daily contact with fellow workers, subject to the current propaganda. The situation was arriving at a stage when the consciences of Catholics were seriously perturbed as to whether their loyalty to their Church and Trade Unions and political Party were being violated. It was significant that an impression was gaining currency that English Catholics who were members of the aristocracy or of non-Labour political parties, made use of the Spanish atrocities (believed to be greatly exaggerated) for purely political ends. Mgr. Hinsley Answers In the course of the two hours' talk — which, it must again be emphasised, had no official mandate or bearing on the official Trade Union or Labour Movement - Mgr Hinsley discussed most frankly and intimately the points raised, evincing the keenest and closest knowledge of the problems raised. He traced in the closest manner the position in Spain since the Reformation — or rather in Europe — and showed that the supposed power and wealth of the Church in Spain was largely a fallacy — the Church having almost been impoverished for over 100 years. Communist Plot Proved He went on to prove that definite evidence was in his possession showing of meetings held in Spain prior to the rising of Franco where plots were hatched and prepared for a Red rising early this year — such information being in the hands of the Foreign Office. His Grace stated that atrocities were committed a long time prior to the present rebellion and that the Reds of Moscow had and were using " Democracy " in Spain and elsewhere as a " Trojan Horse " quoting the speech of Dimitrov at a recent World Communist Congress to prove this. Church Not Responsible His Grace admitted that the condition of the Spanish people was far from satisfactory, but strongly denied that this was due to the Church or its influence, although probably the teachings of the Popes on Social Questions might have been more vigorously taught in Spain as perhaps even in England. The Church were no more responsible for the conditions of the Spanish workers as were he and his brother bishops responsible for the condition of the British miners or the Means Test. The Duty of Catholics Mgr. Hinsley, however, deprecated any use of the situation for political ends in this country if such were in fact being made. He reiterated the right, in fact, the duty of Catholics to be in their trade unions and assist the trade union movement to circumscribe the influence of Communism. Fascism Also Condemned He reminded us that the present Pope had condemned the extremes of Fascism as he did Communism and explained the early conflicts with Mussolini on the question of (Continued at foot of next column.) Catholic Youth in Italy. The Pope's influence in Germany was not so great, as it is a Protestant Country. When a further proposal was submitted at the meeting for the setting up of a Catholic Consultative Committee of Catholics who are in the Trade Union and Labour Movement holding positions of responsibility and who are competent to express an opinion to consult with His Grace on matters of appropriate moment that arise from time to time, he suggested that the time was not opportune to form such a Consultative Committee. These things should grow. Mgr. Hinsley. however, stated quite freely, that he approved of the intention and motives of bringing to his notice our doubts and views and promised that he would see us with any of our Catholic companions at any time he was free and able to do so. His Grace concluded by stating he wanted Catholic workers to look upon him as a friend, as a worker himself and as a Father, and upon them as his sons. Delegation Satisfied The deputation subsequently reviewed the result of the interview and expressed its fullest satisfaction with it. Mr. T. O'Brien being deputed to act as Convener in any future matter. 292/946/19/16(i)